Characterisation of subpopulations of chicken mononuclear phagocytes that express TIM4 and the macrophage colony-stimulating factor receptor (CSF1R) - Hu, Tuanjun (J Immunol, 2019)
The phosphatidylserine receptor, TIM4, encoded by TIMD4, mediates the phagocytic uptake of apoptotic cells. We applied anti-chicken TIM4 monoclonal antibodies, in combination with CSF1R reporter transgenes to dissect the function of TIM4 in the chick (Gallus gallus). During development in ovo, TIM4 was present on the large majority of macrophages but expression became more heterogeneous post-hatch. Blood monocytes expressed KUL01, class II MHC and CSF1R-mApple uniformly. Around 50% of monocytes were positive for surface TIM4. They also expressed many other monocyte-specific transcripts at a higher level than TIM4(-) monocytes. In liver, highly-phagocytic TIM4(hi) cells shared many transcripts with mammalian Kupffer cells and were associated with uptake of apoptotic cells. Although they expressed CSF1R mRNA, Kupffer cells did not express the CSF1R-mApple transgene, suggesting that additional CSF1R transcriptional regulatory elements are required by these cells. By contrast, CSF1R-mApple was detected in liver TIM4(lo) and TIM4(-) cells which were not phagocytic and were more abundant than Kupffer cells. These cells expressed CSF1R, alongside high levels of FLT3, MHCII, XCR1 and other markers associated with conventional dendritic cells (cDC) in mice. In bursa, TIM4 was present on the cell surface of two populations. Like Kupffer cells, bursal TIM4(hi) phagocytes co-expressed many receptors involved in apoptotic cell recognition. TIM4(lo) cells appear to be a sub-population of bursal B cells. In overview, TIM4 is associated with phagocytes that eliminate apoptotic cells in the chick. In the liver, TIM4 and CSF1R reporters distinguished Kupffer cells from an abundant population of DC-like cells.